Evaluation of ERA5-Land reanalysis datasets for extreme temperatures in the Qilian Mountains of China - Zhao, Peng; He, Zhibin; Ma, Dengke; Wang, Wen (Frontiers in Ecology and Evolution, 2023)
An increase in extreme temperature events could have a significant impact on terrestrial ecosystems. Reanalysis temperature data is an important data set for extreme temperature estimation in mountainous areas with few weather stations. The ability of ERA5-Land reanalysis to capture the extreme temperature index published by the Expert Team on Climate Change Detection and Indices (ETCCDI) was evaluated by using the observation data from 17 meteorological stations in the Qilian Mountains (QLM) during 1979-2017. The results show that the ERA5-Land reanalysis temperature data can capture well the daily maximum temperature, two warm extremes (TXx and TX90p) and one cold extreme (FD0) in the QLM. ERA5-Land's ability to capture temperature extremes is best in summer and worst in spring and winter. In addition, ERA5-Land captures trends in all extreme temperature indices except the daily temperature range (DTR). The main bias of ERA5-Land is due to the difference in elevation between the ground observation station and the ERA5-Land grid point. The simulation accuracy of ERA5-Land increases with the decrease of elevation difference. The results can provide reference for the study of local extreme temperature by using reanalysis data.